Pemberdayaan Ekonomi Masyarakat melalui Pelatihan Produk UMKM Kripik Pisang Coklat Lumer, Gabin Fla Susu, dan Spray Anti Nyamuk di Desa Cot Trap, Aceh Jaya - Vila Handayani; Titi Yuni Sartika; Zulfikar Zulfikar; Fajriati Fajriati; Hayatun Nufus; Reza Wati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The Student Community Service Program (KKN) is a form of community service aimed at enhancing community capacity and self-reliance through empowerment activities. This KKN program was implemented in Cot Trap Village under the theme